2020
DOI: 10.3390/vaccines8010054
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of HIV-1 Vaccines Expressing Chimeric Envelope Glycoproteins on the Surface of Pr55 Gag Virus-Like Particles

Abstract: The HIV-1 envelope glycoprotein (Env) is present on the surface of the virion at a very low density compared to most other enveloped viruses. Substitution of various parts of the stalk domain of Env (gp41) with the corresponding elements from other viral glycoproteins has been shown to increase Env spike density on the cell membrane and surface of virus-like particles (VLPs). In this study, chimeric Env antigens were generated by replacing the transmembrane and cytoplasmic domains of HIV-1 Env with the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…The enhanced incorporation of MMTV-TMCT- and HA-TMCT-modified Env were broadly consistent with the improved incorporation reported when the same substitutions were used with insect-cell-produced HIV-1 VLPs [ 33 ], although the HA-TMCT enhanced incorporation more efficiently in this study. These results also contrasted with a study incorporating similar Env/HA-TMCT constructs into Gag-only VLPs that showed no improvement over wild-type Env [ 105 ]. These differences are probably reflective of the different cell lines and VLP expression vectors used.…”
Section: Discussioncontrasting
confidence: 88%
“…The enhanced incorporation of MMTV-TMCT- and HA-TMCT-modified Env were broadly consistent with the improved incorporation reported when the same substitutions were used with insect-cell-produced HIV-1 VLPs [ 33 ], although the HA-TMCT enhanced incorporation more efficiently in this study. These results also contrasted with a study incorporating similar Env/HA-TMCT constructs into Gag-only VLPs that showed no improvement over wild-type Env [ 105 ]. These differences are probably reflective of the different cell lines and VLP expression vectors used.…”
Section: Discussioncontrasting
confidence: 88%
“…The expression of the Env and Gag proteins in cells infected with the LSDV vaccine was confirmed by Western blotting and immunofluorescent staining (Figure 2). In vitro expression of Env and Gag has previously been confirmed for the DNA and MVA vaccines [34,36].…”
Section: Expression Of Env and Gagmentioning
confidence: 83%
“…All four human monoclonal antibodies (CAP256 VRC26.08, PGT128, VRC01, and PG9) tested, bound, to some extent, to the Env expressed by LSDVGC5 (Figure 3). The live cell staining of the cells transfected with the DNA vaccine or infected with the MVA vaccine was carried out previously with a larger panel of monoclonal antibodies [34,36]. A summary of the live cell staining results for the Env expressed by all three vaccines (DNA, MVA, and LSDV) is given in Figure 3b.…”
Section: Quaternary Structure Of Env Expressed In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Research efforts in South Africa have resulted in the development of a number of candidate HIV-1 vaccines [ 32 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] including SAAVI DNA-C2 and SAAVI MVA-C, the only two African-produced candidates ever to have successfully moved from basic research to Phase 1 clinical trials [ 54 , 55 ]. These efforts have also led to the establishment of the Chacma baboon and ChRM as nonhuman primate models for the immunogenicity evaluation of these vaccine candidates [ 32 , 39 , 40 , 43 , 44 , 45 , 56 ].…”
Section: Discussionmentioning
confidence: 99%